Sex as a biological variable in the pathology and pharmacology of neurodegenerative and neurovascular diseases - Honarpisheh, Pedram (Br J Pharmacol, 2019)
The incidence of dementia, most commonly caused by cerebrovascular and neurodegenerative diseases, continues to grow as our population ages. Alzheimer disease (AD) and vascular cognitive impairment (VCI) are responsible for more than 80% of all cases of dementia. There are few effective, long‐term treatments for AD and VCI‐related conditions (e.g., stroke and cerebral amyloid angiopathy (CAA)). This review focuses on AD (as the most common “neurodegenerative” cause of dementia), CAA (as an “emerging” cause of dementia), and stroke (as the most common cause of “vascular” dementia). We will discuss the available literature on the pharmacological therapies that demonstrate sex differences, which refer to any combination of structural, chromosomal, gonadal, or hormonal differences between males and females. We will emphasize the importance of considering sex as a biological variable in the design of preclinical and clinical studies that investigate underlying pathologies or response to pharmacological interventions in dementia. LINKED ARTICLES: This article is part of a themed section on The Importance of Sex Differences in Pharmacology Research. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v176.21/issuetoc